Circuit Modelling of Bandpass/Channel Filter with Microstrip Implementation - Augustine Onyenwe Nwajana (IAES Indonesian Section, 2020)
This paper presents a step-by-step approach to the design of bandpass/channel filters. A 3-pole Chebyshev bandpass filter (BPF) with centre frequency of 2.6 GHz, fractional bandwidth of 3%, passband ripple of 0.04321 dB and return loss of 20 dB has been designed, implemented, and simulated. The designed filter implementation is based on the Rogers RT/Duroid 6010LM substrate with a 10.7 dielectric constant and 1.27 mm thickness. The BPF was also fabricated using the same substrate material used for the design simulation. The circuit model and microstrip layout results of the BPF are presented and show good agreement. The microstrip layout simulation results show that a less than 1.8 dB minimum insertion loss and a greater than 25 dB in-band return loss were achieved. The overall device size of the BPF is 18.0 mm by 10.7 mm, which is equivalent to 0.16λg x 0.09λg, where λg is the guided wavelength of the 50 Ohm microstrip line at the filter centre frequency.